Hypermethylation of MEG3 promoter correlates with inactivation of MEG3 and poor prognosis in patients with retinoblastoma - Yali Gao; Peng Huang; Jun Zhang (Journal of Translational Medicine, 2017)
Abstract Background In our previous study, we revealed that MEG3 was a tumor suppressor gene in retinoblastoma and inhibited proliferation of retinoblastoma cells by regulating the activity of the Wnt/β-catenin pathway. Here, we further explored the mechanism of MEG3 inactivation in retinoblastoma. Methods MSP and qRT-PCR were performed to detect the methylation status of MEG3 promoter and levels of MEG3 expression, respective. To further explore relationship between MEG3 expression and epigenetic modifications, 5-Aza-CdR was used to interfere with DNA methylation. In addition, we evaluated proliferation, apoptosis and the expression of β-catenin via CCK-8, flow cytometric analysis and western blot analysis, respective. Results Hypermethylation of MEG3 promoter was observed more frequently in retinoblastoma tissues and was highly associated with low MEG3 expression and poor survival of retinoblastoma patients. We also provided evidence demonstrating that hypermethylation of MEG3 promoter depressed MEG3 expression, promoted proliferation, inhibited apoptosis and increased β-catenin expression of retinoblastoma cells in vitro. Conclusions Our present study indicates that promoter silencing by hypermethylation may account for the loss of MEG3 expression and predict poor prognosis.